Factors associated with the delay in diagnosis of extrapulmonary tuberculosis at the patient and health system level: A study from a rural setting in India. - Shoaib Hassan; Reza Yaesoubi; Ole Bjørgaas Helle Magnus; Mala Kanthali; Manju Raj Purohit; Tehmina Mustafa (PLoS ONE)
Background With the proportion of tuberculosis cases that are extrapulmonary tuberculosis (EPTB) increasing in recent years, understanding and addressing factors contributing to the prolonged time to diagnosis (TTD) of EPTB patients is vital. Methods We enrolled presumptive EPTB patients for a cohort study from 2018-2020 in Ujjain, India. Based on a structured questionnaire, the patients were interviewed for socio-demographic and clinical information, including previously visited health facilities (HF) for this illness. We analysed patients' TTD, healthcare access, and referral pathways. Findings EPTB (54%) and non-TB (58%) patients visited dispensaries during their first visit to a formal HF. Patients visited multiple HFs, including dispensaries (54%) and regional hospitals (32%), during 1-4 visits but did not receive an appropriate diagnosis. Less than 2% of the patients accessed private HFs. Most of the adult EPTB (83%) and non-TB (76%) patients were self-referred to our study site, where they were diagnosed. Our statistical models highlighted low-middle income groups, longer distances and longer travel time to HFs, and potentially less-empowered occupations as housewives with a prolonged TTD. Patients with a longer wait, including travel time, had a shorter TTD. Conclusion We found individual, societal-level, and structural barriers to healthcare access and utilisation and their association with diagnostic delay among adult and paediatric EPTB patients.